Molecular diversity and evolution of far-red light-acclimated photosystem I - Gisriel, Christopher J.; Bryant, Donald A.; Brudvig, Gary W.; Cardona, Tanai (Frontiers in Plant Science, 2023)
The need to acclimate to different environmental conditions is central to the evolution of cyanobacteria. Far-red light (FRL) photoacclimation, or FaRLiP, is an acclimation mechanism that enables certain cyanobacteria to use FRL to drive photosynthesis. During this process, a well-defined gene cluster is upregulated, resulting in changes to the photosystems that allow them to absorb FRL to perform photochemistry. Because FaRLiP is widespread, and because it exemplifies cyanobacterial adaptation mechanisms in nature, it is of interest to understand its molecular evolution. Here, we performed a phylogenetic analysis of the photosystem I subunits encoded in the FaRLiP gene cluster and analyzed the available structural data to predict ancestral characteristics of FRL-absorbing photosystem I. The analysis suggests that FRL-specific photosystem I subunits arose relatively late during the evolution of cyanobacteria when compared with some of the FRL-specific subunits of photosystem II, and that the order Nodosilineales, which include strains like Halomicronema hongdechloris and Synechococcus sp. PCC 7335, could have obtained FaRLiP via horizontal gene transfer. We show that the ancestral form of FRL-absorbing photosystem I contained three chlorophyll f-binding sites in the PsaB2 subunit, and a rotated chlorophyll a molecule in the A0B site of the electron transfer chain. Along with our previous study of photosystem II expressed during FaRLiP, these studies describe the molecular evolution of the photosystem complexes encoded by the FaRLiP gene cluster.